2020
DOI: 10.3324/haematol.2019.245407
|View full text |Cite
|
Sign up to set email alerts
|

Elastography improves accuracy of early hepato-biliary complications diagnosis after allogeneic stem cell transplantation

Abstract: Significant morbidity and mortality have been associated with liver complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Causes and consequences of these hepato-biliary complications are various and might be life-threatening. A high misdiagnosis rate has been reported because of a weak correlation between clinical, laboratory and imaging data. Liver elastography, a liver stiffness measure, is able to assess liver fibrosis and portal hypertension in most liver diseases, but data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…LSM gradually decreased following successful specific SOS/VOD treatment. These findings were confirmed by another group that performed transient elastography before alloHCT, at day +7 and day +14 in 146 patients [28]. They found that a significant increase at day +14 allowed early detection of SOS (AUROC = 0.84, p = 0.004) with a high sensibility (75%) and specificity (99%).…”
Section: Diagnosis Criteriamentioning
confidence: 62%
“…LSM gradually decreased following successful specific SOS/VOD treatment. These findings were confirmed by another group that performed transient elastography before alloHCT, at day +7 and day +14 in 146 patients [28]. They found that a significant increase at day +14 allowed early detection of SOS (AUROC = 0.84, p = 0.004) with a high sensibility (75%) and specificity (99%).…”
Section: Diagnosis Criteriamentioning
confidence: 62%
“…Second, not all cases were histologically confirmed to have SOS/VOD. Third, elastography [29,30] was not performed at our institution; thus, its efficacy and contribution, compared with ultrasound remain unknown. Despite these limitations, this study is valuable in point of the first report indicating the utility of the refined EBMT criteria 2023.…”
Section: Discussionmentioning
confidence: 99%
“…This method is called non-invasive liver biopsy. It can be used at various time points: at the initial stage to assess the risk of SOS/VOD, after HSCT to diagnose SOS/VOD and later to monitor the treatment course [57,58]. Other imaging techniques are also used in the diagnosis of SOS/VOD, such as computed tomography (CT), which is useful in confirming the diagnosis of SOS/VOD, or magnetic resonance imaging (MRI), which is used to assess the risk based on the iron load in the patient's body [57].…”
Section: Diagnostic Techniquesmentioning
confidence: 99%